Ultrasound Asymptomatic Carotid Plaque Image Analysis for the Prediction of the Risk of Stroke - Loizou, Christos P.; Kyriacou, Efthivoulos (My University, 2019)
High-resolution vascular B-mode and Doppler ultrasound provide information not only on the degree of carotid artery stenosis but also on the characteristics of the arterial wall including the size and consistency of atherosclerotic plaques [1]. Carotid stenosis alone has limitations in predicting risk and does not show plaque vulnerability and instability, thus other ultrasonographic plaque morphologic characteristics have been studied for better prediction of the risk stroke. Plaque echogenicity as assessed by B-mode ultrasound has been found to reliably predict the content of soft tissue and the amount of calcification in carotid plaques. Additionally, it has been reported that subjects with echolucent atherosclerotic plaques have increased risk of ischemic cerebrovascular events [2]. More recent studies by Nicolaides et al. [3] Topakian et al. [4] and Kyriacou et al. [5], showed that plaque echolucency and plaque morphology can be used to predict stroke. Other studies have reported that plaques that are more echolucent and heterogeneous are often associated with higher cerebrovascular risk and the development of ipsilateral neurological symptoms [3, 6, 7, 8, 9, 10]. In contrast, homogeneous hypoechoic and hyperechoic plaques without evidence of ulceration usually remain asymptomatic.
Keywords: Doppler ultrasound; Carotid artery stenosis; Atherosclerotic plaques; B-mode ultrasound; Risk modeling SVM; Cerebrovascular risk